2020
DOI: 10.1093/gigascience/giaa038
|View full text |Cite
|
Sign up to set email alerts
|

Species-level evaluation of the human respiratory microbiome

Abstract: Background Changes to human respiratory tract microbiome may contribute significantly to the progression of respiratory diseases. However, there are few studies examining the relative abundance of microbial communities at the species level along the human respiratory tract. Findings Bronchoalveolar lavage, throat swab, mouth rinse, and nasal swab samples were collected from 5 participants. Bacterial ribosomal operons were seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…Histamine, a key metabolite involved in local host responses, was significantly accumulated by infection with V. atypica and V. montpellierensis. Other studies have found that histamine can decrease the expression of tight junctional proteins (ZO-1 in nasal epithelial cells and E-cadherin in epithelial pulmonary cells) 61 . Therefore, an increase in histamine may increase epithelial permeability, although this would need to be tested in the context of the cervicovaginal epithelium to confirm the role of histamine in barrier function within the cervicovaginal mucosa.…”
Section: Discussionmentioning
confidence: 92%
“…Histamine, a key metabolite involved in local host responses, was significantly accumulated by infection with V. atypica and V. montpellierensis. Other studies have found that histamine can decrease the expression of tight junctional proteins (ZO-1 in nasal epithelial cells and E-cadherin in epithelial pulmonary cells) 61 . Therefore, an increase in histamine may increase epithelial permeability, although this would need to be tested in the context of the cervicovaginal epithelium to confirm the role of histamine in barrier function within the cervicovaginal mucosa.…”
Section: Discussionmentioning
confidence: 92%
“…In our study, there is a tendency of association of the species V. dispar with a better lung function (non-significant association). The lung role of this species in PWCF is as yet unknown but a recent study in healthy people has shown that lung bacteria are the same as oral or nasal bacteria, but that some, like V. dispar , are enriched in the healthy lung 40 . This finding suggests that V. dispar may play an important role in lung health 40 , which needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The lung role of this species in PWCF is as yet unknown but a recent study in healthy people has shown that lung bacteria are the same as oral or nasal bacteria, but that some, like V. dispar , are enriched in the healthy lung 40 . This finding suggests that V. dispar may play an important role in lung health 40 , which needs further investigation. These results also pave the way for discussion of the protective role of anaerobic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Along similar lines, Ibironke et al . ( 2020 ) examined the bacterial component in four compartments in the human respiratory system (lung [via lavage], throat, mouth and nose) from five subjects. The aim was to delineate the microbes that colonize the lungs, rather than being passively transported via inhalation.…”
Section: Additional Equipment Required For Use In the Fieldmentioning
confidence: 99%